Formation, evolution, and enhancement mechanisms of mixed temperature gradient during interfacial solar vapor generation. (July 2023) - Li, Yan; Liu, Xiaoyi; Hong, Wenpeng; Chen, Xu; Li, Haoran
Highlights: The mixed temperature gradient of the solar evaporator was simulated and revealed. The interface between positive and negative temperature gradients was demarcated. Different energy inputs and their contribution to the evaporation flux were quantified. The mixed temperature gradient appears at the evaporation area index of δ > 2.21. The heat supplied by bulk water to the solar absorber remains stable at δ ≥ 13.12. Abstract: The solar evaporator, which generates a mixed temperature gradient (MTG) in the process of solar-driven interfacial water evaporation (SIWE), has shown great application potential in clean water production. It is also expected to provide a more comprehensive understanding to shed light on the formation, evolution, and enhancement mechanisms of the MTG. Herein, the space-time evolution of the solar absorber temperature and the evaporation performance in the column solar absorber are studied through a three-dimensional and multi-physical model coupling heat transfer and water transport. The results will demonstrate not only the temperature distribution during the SIWE process but the interface between positive temperature gradient (PTG) and negative temperature gradient (NTG). Moreover, the relationship between evaporation rate and light intensity, bulk water temperature, and environment humidity will be investigated. Importantly, the contributions of solar heating, PTG, NTG, and environment heating to the total evaporation rate will be quantitatively analyzed. Finally, based on the above results, the formation conditions, evolution characteristics, and enhancement mechanisms of MTG will be revealed. This paper will provide theoretical guidance for the successful construction and operation of an MTG evaporator for SIWE acceleration.